2018
DOI: 10.1371/journal.pone.0191614
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative and qualitative normative dataset for intraepidermal nerve fibers using skin biopsy

Abstract: BackgroundSkin biopsy is the most relevant tool to diagnose small-fiber neuropathy. A well-documented normal dataset for intraepidermal nerve fiber in the distal leg is required to improve its diagnostic value.MethodsThree hundred healthy subjects were enrolled in the study, after clinical and biological screening to exclude neurological and systemic pathologies. A distal leg biopsy was taken and intraepidermal nerve fiber density after protein gene product-9.5 immunocytochemistry with brightfield microscopy w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 28 publications
(36 reference statements)
3
25
0
Order By: Relevance
“…10 IENF density was assessed with bright-field immunohistochemistry. In this patient, a reduced IEFN density was shown at distal leg 3.03 IENF/mm (lower fifth percentile normal IENF density for the age and gender, as defined by Collongues et al 6 , is 4.9 IENF/mm). Extensive explorations were made to find the origin, although none was found, and she was diagnosed with idiopathic small fiber neuropathy.…”
Section: Methodssupporting
confidence: 49%
See 1 more Smart Citation
“…10 IENF density was assessed with bright-field immunohistochemistry. In this patient, a reduced IEFN density was shown at distal leg 3.03 IENF/mm (lower fifth percentile normal IENF density for the age and gender, as defined by Collongues et al 6 , is 4.9 IENF/mm). Extensive explorations were made to find the origin, although none was found, and she was diagnosed with idiopathic small fiber neuropathy.…”
Section: Methodssupporting
confidence: 49%
“…10 A more recent study published new intraepidermal nerve fiber (IEFN) density normative values for clinical use for each year of age and patients' sex. 6…”
Section: Introductionmentioning
confidence: 99%
“…201 It is a reproducible and reliable technique with a specificity greater than 90%, sensitivity approaching 80%, and favorable positive and negative predictive values 12202203204. Multiple large cohort studies have been conducted to establish normative values for IENFD at the distal leg because age, ethnicity, and sex are known to produce variations 202203205. A recent longitudinal case-control study showed that rates of IENFD decrease are similar at proximal and distal biopsy sites, regardless of cause, supporting a non-length dependent process 41.…”
Section: Diagnostic Approachmentioning
confidence: 99%
“…In healthy subjects, IENFD is known to decrease with age, whereas women have higher IENFDs compared with men of the same age ( Collongues et al , 2018 ). In previous studies, IENFD has consistently been reported to be decreased in biopsies from the distal leg or the fingertips in CMT1A ( Nolano et al , 2015 ; Duchesne et al , 2018 ).…”
Section: Introductionmentioning
confidence: 99%